An Investigation into Multi-Spinning Process with Telescopic Mandrel - Hammad T. Elmetwally, Essam K. Saied, Ayman A. Abd-Eltwab, Shaimaa G. Elglaab (International Journal of Advanced Science and Technology, 2019)
Conventional multi-stage spinning is a process used widely in manufacturing to obtain cup shape products. A proposed compound tool with telescopic mandrel was developed before to achieve the process of multi spinning at one pass, this technique still needs investigation in the area of optimization. In this research, an investigation into the effect of process parameters of the compound multi-spinning tool with telescopic mandrel was conducted. The experimental work was carried out on the center lathe machine using spinning rollers installed on a dynamometer replaced the tool post while the telescopic mandrel was mounted on the lathe chuck. The process parameters such as the rotational speed of telescopic mandrel and the feed rate of the spinning roller effect on the spinning ratio, process load, and the product quality were investigated. The experimental results showed that mandrel rotational speed and axial feed affected the process load, the spinning ratio, and the product quality.